New Perspective in Elderly Care - Farnicka, Marzanna (Magyar Gerontológia, 2025)
The aging of European societies requires new perspectives on old adults care that move beyond traditional medical approaches. This paper examines multidimensional frameworks supporting the well-being of older adults, based on comparative demographic data from Poland, Hungary, and the European Union. The analysis highlights both similarities and differences in life expectancy, health, and living conditions among people aged 65 and over. Empirical studies demonstrate that physical, psychological, social, and environmental dimensions of well-being are strongly interrelated. Psychological resources such as optimism, resilience, and positive beliefs about aging have measurable biological and behavioral effects. Equally vital are social participation and age-friendly environments that promote autonomy and dignity. The paper as a conceptual paper argues for a holistic, interdisciplinary, and participatory model of care in late adulthood that integrates medical, psychological, and social perspectives. Such an approach offers a sustainable path toward healthy, meaningful, and dignified aging in contemporary European societies.